Revitalizing Ihsaniah Iskandariah Mosque: heritage conservation, challenges, and opportunities - Wan Mohd Azmi, Wan Faida; Syed Mustapa, Syed Abdul Haris; Ab Wahab, Lilawati; Baharuddin, Mohd Nurfaisal; Musa, Muhammad Suhaimi (2025)
The Ihsaniah Iskandariah Mosque in Kampung Kuala Dal, Perak, is a significant cultural and architectural landmark, built in 1936. The mosque is renowned for its unique bamboo panel walls (kelarai) and its fusion of traditional Malay craftsmanship with Islamic architectural influences. However, the mosque faces challenges of structural deterioration, especially with its bamboo walls succumbing to environmental damage and pests, and it is underutilized by the local community. Despite conservation efforts, the mosque remains mostly inactive, used only for occasional religious events. The revitalization of the mosque is essential for preserving its historical and cultural value while transforming it into a vibrant community hub. Strategies for this include preserving its architectural integrity through eco-friendly materials and techniques, such as thermochemical compression densification, to enhance durability. Furthermore, fostering community engagement through educational workshops, cultural events, and heritage tours can help strengthen the mosque's role as a space for learning, cultural exchange, and tourism. Revitalization can drive local economic growth and tourism while deepening community pride and intergenerational cultural connections. By involving the community and leveraging modern technologies, the mosque can thrive as a living heritage site.